Two-dimensional electromagnetically induced grating via gain and phase modulation in a two-level system. (29th March 2016) - Cheng, Guang-Ling; Cong, Lu; Chen, Ai-Xi
Abstract: A scheme for two-dimensional (2D) electromagnetically induced grating via spatial gain and phase modulation is presented in a two-level atomic system. Based on the interactions of two orthogonal standing-wave fields, the atom could diffract the weak probe beam into high-order directions and a 2D diffraction grating is generated. It is shown that the diffraction efficiency of the grating can be efficiently manipulated by controlling the Rabi frequencies of control fields, the detunings of the control and probe fields, and interaction length. Different from 2D cross-grating via electromagnetically induced transparency in a four-level atomic system, the present scheme results from the spatial modulation of gain and phase in a simple two-level system, which could lead to 2D gain-phase grating with larger diffraction intensities in the diffraction directions. The studies we present may have potential applications in developing photon devices for optical-switching, optical imaging and quantum information processing.